METODE PENGAJARAN GURU BAHASA MANDARIN DANPENGARUHNYA TERHADAP PRESTASI BAHASA MANDARIN SISWA KELAS TUJUH SMP BHINNEKA TUNGGAL IKAYOGYAKARTA - , FOMBAGI DODO LAIA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This graduating paper is entitled \"Teaching Method of Chinese used by Teacher and the Influenceon Achievement for 7th Grade Students in Yogyakarta Bhinneka Tunggal Ika Junior High Schoolâ it aims to know realization of the teaching of Chinese language teacher for 7th grade students in Yogyakarta Bhinneka Tunggal Ika Junior High School. The method used in this the is observation, interviews and study literatur. The inclusion of Chinese language lessons into the curriculum in Yogyakarta Bhinneka Tunggal Ika Junior High School aims to equip the learners in their knowledge and to add knowledge of students learning Chinese language. The proces of teaching Chinese language teacher for 7th grade students in Yogyakarta Bhinneka Tunggal Ika Junior High School generally going well. The methods are applied to a teacher lecture, among other methods, the method of memorizing vocabulary, and answer method, and the method review or repeat. In addition, the on going proces of teaching can also determine the factor that influence achievement for into Chinese language for 7th graders in Yogyakarta Bhinneka Tunggal Ika Junior High School.